1996
DOI: 10.1046/j.1365-2265.1996.705526.x
|View full text |Cite
|
Sign up to set email alerts
|

Wasting in the acquired immune deficiency syndrome is associated with multiple defects in the serum insulin‐like growth factor system

Abstract: AIDS wasting is associated with a GH resistant state that results in low levels of serum IGF-I, IGF-II and IGFBP-3, elevated levels of phosphorylated IGFBP-1, and a reduced ability to form the IGFBP-3 ternary complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 26 publications
1
32
1
1
Order By: Relevance
“…Candidate hormones with effects on protein catabolism are growth hormone, thyroid hormones, steroids, insulin, and others. Studies have shown that there is a profound dysregulation in some of these systems in patients with advanced HIV disease and especially with AIDS wasting (1,6,7,9,10,19,23). In these patients, lean body mass (proteins and carbohydrates) is being converted into fat, a process which may also impact the degradation of ENF.…”
Section: Resultsmentioning
confidence: 99%
“…Candidate hormones with effects on protein catabolism are growth hormone, thyroid hormones, steroids, insulin, and others. Studies have shown that there is a profound dysregulation in some of these systems in patients with advanced HIV disease and especially with AIDS wasting (1,6,7,9,10,19,23). In these patients, lean body mass (proteins and carbohydrates) is being converted into fat, a process which may also impact the degradation of ENF.…”
Section: Resultsmentioning
confidence: 99%
“…(38) reported that, in protein-restricted rats, the proportion of IGF-I in smaller molecular mass complexes (ϳ30 kDa), as measured by size-exclusion HPLC, increased from ϳ33% during control to 65% after protein restriction. Certain pathophysiological conditions (i.e., growth hormone deficiency, starvation, tumor hypoglycemia) have also shown that the ratio of IGF-I bound to the ternary vs. binary complexes is decreased (12,16,17). Furthermore, recent studies (29,35) have demonstrated that both acute exercise and chronic physical training can increase circulating concentrations of low molecular mass IGFBPs.…”
mentioning
confidence: 99%
“…IGF-I is a GH-dependent anabolic hormone that stimulates protein synthesis and strongly reduces protein breakdown (Fryburg 1994). Decrease in circulating IGF-I has been reported in most catabolic situations (Ross et al 1991, Frost et al 1996, Timmins et al 1996. Furthermore, exogenous GH and IGF-I have also been reported to improve nitrogen balance in some of these situations (Mulligan et al 1993, Berneis et al 1997.…”
Section: Introductionmentioning
confidence: 99%